2019
DOI: 10.1111/jtxs.12454
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of casein micelle size and calcium and citrate content on rennet‐induced coagulation in bovine milk

Abstract: Interactive effects of casein micelle size and milk calcium and citrate content on rennet‐induced coagulation were investigated. Milk samples containing small (SM) and large (LM) micelles, obtained from individual Holstein cows, were modified by addition of calcium and/or citrate and milk coagulation properties were evaluated in a full factorial design. The results showed that LM milk had a higher relative proportion of casein, coagulated faster, and resulted in a stronger gel than SM milk. Addition of calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
(66 reference statements)
5
16
0
Order By: Relevance
“…Rennet coagulation time and G20 are generally inversely related; milk that coagulates rapidly (low RCT) has higher gel strength (high G20). This is visualized in the PCA in Figure 3B, where RCT and G20 are located on opposite sides in the loading plot, previously also reported by Priyashantha et al (2019). Hallén et al (2007) investigated the rheological properties of individual milk samples from SRB and SH and observed that protein concentration was positively associated with G20, but not with RCT, also confirming our observations.…”
Section: Variation In Milk Quality Attributes Associated With Farm Typesupporting
confidence: 90%
See 2 more Smart Citations
“…Rennet coagulation time and G20 are generally inversely related; milk that coagulates rapidly (low RCT) has higher gel strength (high G20). This is visualized in the PCA in Figure 3B, where RCT and G20 are located on opposite sides in the loading plot, previously also reported by Priyashantha et al (2019). Hallén et al (2007) investigated the rheological properties of individual milk samples from SRB and SH and observed that protein concentration was positively associated with G20, but not with RCT, also confirming our observations.…”
Section: Variation In Milk Quality Attributes Associated With Farm Typesupporting
confidence: 90%
“…Casein micelle size was determined by nanoparticle tracking analysis (NTA) using NanoSight NS500 (Malvern Instruments) according to the method described by Priyashantha et al (2019). The system was coupled to a temperature sensor, stage controller, and syringe pump (Harvard Apparatus) fitted with a 1-mL syringe filled with 2,000-fold diluted skim milk.…”
Section: Casein Micelle Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the interaction effect, the shortest RCT was also recorded with milk from December (361 s), and the longest was 529 s for milk collected in February. The highest G20 was associated with the lowest RCT value, which is in agreement with results reported by Priyashantha et al (2019). The observed differences in G20 could likely to be an effect of variation in protein content (e.g., higher protein resulted in stronger gel compared with lower protein content; Panthi et al, 2019).…”
Section: Variation In Milk Quality Attributes Associated With Sampling Monthsupporting
confidence: 88%
“…The pH of milk samples was measured using a pH meter (Seven Compact S210) at room temperature. Average casein micelle size was determined by nanoparticle tracking analysis using NanoSight NS500 (Malvern Instruments) according to the method described by Priyashantha et al (2019). Rennet-induced coagulation properties of skim milk were evaluated using a Bohlin CVOR-150-900 rheometer (Malvern Instruments Nordic AB) according to Johansson et al (2015) using calf rennet (75/25 chymosin/bovine pepsin, 180 international milk clotting units, Kemikalia) at a concentration of 0.18 international milk clotting units per milliter.…”
Section: Milk Characterizationmentioning
confidence: 99%